Prediction of preterm delivery with a novel bedside test - Vishwekar, Pallavi S.; Chauhan, Anahita R.; Turakhia, Naju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preterm birth occurs in 7 to 12 % of all deliveries but account for 85% of perinatal morbidity and mortatity. Hence, there is a need for a reliable test to predict the onset of preterm labour. One such test is detection of phosphorylated insulin like growth factor binding protein 1 (phIGFBP- 1) in cervical secretion with a simple bedside kit that is recently commercialized Actim Partus kit. Methods: This was a prospective study carried out at a tertiary hospital over a period of 2 years from October 2006 to November 2008. Women between 28 to 37 weeks with intact fetal membranes, who presented with threatened preterm labour were included and followed up till delivery. Time interval between test and delivery, weeks of gestation at the time of delivery, labour and delivery details as well as neonatal outcome were documented. Diagnostic accuracy of the test was determined by sensitivity, specificity, positive and negative predictive value. Results: It was found that this test was extremely sensitive in prediction of preterm delivery and negative test results implied low chance of preterm delivery as in the patients with positive test result the average time of prolongation of pregnancy was less than 24 hours and in patients with negative test result it was more than 7 days which was statistically significant (P value = 0.001). The need for NICU and perinatal morbidity was significantly less in patients with negative test result. Conclusions: There is a role of detection of cervical IGFBP-1 test in the management of women presenting with suspected preterm labour which allows us to focus on patients who are more likely to deliver preterm and also to reduce perinatal mortality and morbidity.